Two Dissertations on Cultural Heritage (ldeological Models of Lithuanian Heritage Protection and Their Practical Expression in the Soviet Periodby Salvijus Kulevičius and Processes of Cultural Heritage in Lithuania in the Soviet and Post-Soviet Periods - Drėmaitė, Marija (Lietuvos istorijos studijos, 2011)
-